2012
DOI: 10.5187/jast.2012.54.5.363
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Supplementation of Garlic and May Flower Powder on CO2and CH4Emission by Hanwoo Cow

Abstract: This study was conducted to investigate the effects of dietary garlic and may flower powder on CO2 and CH4 emission by Hanwoo cows fed TMR (Total Mixed Ration) based diet. Animals were housed in a hood-type respiration chamber and the environmental temperature was maintained at 20℃. Gases were measured for 24 hours using the multi-detector instrument gas monitoring system (Mamos-300, Australia). The treatments composed of groups with no intake of garlic and may flower powder (Control), with intake of garlic at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…However, it is thought to have a simultaneous reduction effect on methane and carbon dioxide emission. This result was similar to that of an in vivo study by Kim, Ha & Song (2012), who reported that the addition of garlic powder to Hanwoo cow diets increased methane and carbon dioxide emission. At 24 h incubation, methane emission and methanogenic archaea abundance decreased linearly.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, it is thought to have a simultaneous reduction effect on methane and carbon dioxide emission. This result was similar to that of an in vivo study by Kim, Ha & Song (2012), who reported that the addition of garlic powder to Hanwoo cow diets increased methane and carbon dioxide emission. At 24 h incubation, methane emission and methanogenic archaea abundance decreased linearly.…”
Section: Discussionsupporting
confidence: 90%
“… Hart et al (2008) reported stable ruminal fermentation patterns as well as significant reductions in both methane output and methanogenic bacteria population. Kim, Ha & Song (2012) reported in vivo methane and carbon dioxide reduction in the rumen after treatment with powdered garlic. Medicinal properties of green welsh onions ( Allium fistulosum L.), especially antifungal and antioxidant properties, were determined; these properties were due to sulfur-containing compounds, flavonoids, fatty acids, and polyphenolic compounds ( Štajner & Milić, 2006 ; Vlase et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation